Preservation of map archives in the National Mapping and Resource Information Authority (NAMRIA) - Go, Chatty Mae M. (2010)
Map is part of our history. It is a vital document that serves as a record of past events and landscapes. It is very important to study how to properly preserve it to prolong its life for future researches. It is in this light that this study focused on the preservation of map archives in the National Mapping and Information Resource Authority (NAMRIA).